Layered oxide positive electrode material of sodium-ion battery as well as preparation method and application of layered oxide positive electrode material

The layered oxide positive electrode material of P2 phase sodium ion battery co-doped with fluoride ions and rare earth metal ions solves the problems of material stability and electrochemical performance in sodium ion batteries, and achieves battery performance with high specific capacity and long life , suitable for large-scale production.

CN119170796AInactive Publication Date: 2024-12-20SUZHOU UNIV

Patent Information

Application Number
CN202411658740.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-20
Publication Date
2024-12-20
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The layered oxide positive electrode material in sodium ion batteries has poor air stability, long cycle life, high specific energy and high rate performance, and the Jahn-Teller effect caused by Mn3+ and side reactions with electrolyte.

Method used

The P2-phase sodium ion battery layered oxide positive electrode material is used to co-dopize fluoride ions and rare earth metal ions. The oxygen position of some fluoride ions and the transition metal ions occupy the transition metal position, forming an octahedral structure with the sodium ion layer or Coplanar connection, combined with high-temperature solid phase method preparation method.

Benefits of technology

It significantly improves the structural stability and electrochemical properties of the material, enhances cycle stability and discharge specific capacity, extends the service life of the battery, and reduces the preparation cost, making it suitable for large-scale production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119170796A_ABST
    Figure CN119170796A_ABST
Patent Text Reader

Abstract

The invention discloses a sodium ion battery layered oxide positive electrode material and a preparation method and application thereof, the sodium ion battery layered oxide positive electrode material is Na < 0.67 > MnaFebNicMxO2-yF2y, M is a rare earth metal element, 0.55 < = a < = 0.65, 0.1 < = b < = 0.2, 0.05 < = c < = 0.15, 0 < x < = 0.1, and 0 < y < = 0.1. The fluorine ion and rare earth metal ion co-doped P2-phase sodium ion battery layered oxide positive electrode material prepared by adopting a simple high-temperature solid phase method is high in specific capacity, good in cycling stability, more stable when exposed in air, simple and convenient in preparation process, low in cost, environment-friendly and suitable for large-scale production. According to the layered oxide positive electrode material for the sodium-ion battery, the specific discharge capacity of the material can be improved, meanwhile, the cycling stability is remarkably improved, and the service life of the battery can be prolonged.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of sodium ion battery electrode materials, and in particular to a sodium ion battery layered oxide positive electrode material and a preparation method and application thereof. Background Art

[0002] Lithium-ion batteries (LIBs) are currently the most promising electrochemical energy storage system, but due to the limited reserves and uneven distribution of lithium resources, lithium-ion batteries are expensive and difficult to meet the needs of the large-scale energy storage market. In contrast, sodium-ion batteries (SIBs) have a similar working principle to lithium-ion batteries, and sodium resources are abundant and widely distributed, so they have significant advantages in cost and are very suitable for large-scale energy storage needs.

[0003] In sodium-ion batteries, the development of cathode materials is crucial for their practical application. Among them, layered oxides have become the mainstream due to their high energy density, excellent voltage platform and good rate performance. Layered oxides can be divided into P2 type and O3 type according to the arrangement order of oxygen atoms. + The P-type and O-type are distinguished by occupying the triangular prism position and octahedral position of the sodium layer (NaO2) respectively. Among them, the P2 phase manganese-based positive electrode material has the advantages of a wide range of raw material sources, environmental friendliness, abundant resources, excellent rate performance, high specific capacity and high operating voltage. On this basis, the electrochemical properties of the material can be further optimized by introducing appropriate amounts of other transition metal elements such as nickel and iron to produce synergistic effects. Specifically, by precisely adjusting the composition ratio of nickel, iron and manganese, the overall electrochemical performance of nickel-iron-manganese-based hierarchical oxide positive electrode materials can be significantly improved.

[0004] However, such layered oxides still have the following difficult-to-solve problems: poor air stability, difficulty in balancing long cycle life with high specific energy and high rate performance, and the Mn content in manganese-based layered cathode materials. 3+ The Jahn-Teller effect caused by the electrolyte and the side reactions with the electrolyte. In order to solve these problems, a series of effective research work is needed. For example, the structure of the material is optimized through morphology design, the stability of the material is improved by surface coating technology, the electrochemical performance is improved by doping and coating integration methods, the stability of the material is enhanced by bulk substitution, and the crystal structure is optimized to improve the overall performance. Current research mainly focuses on single doping or multiple cation doping at transition metal sites and oxygen sites, as well as the co-doping technology of common metal cations and anions. However, there are few reports on the co-doping of fluoride ions and rare earth metal ions. Summary of the invention

[0005] In order to solve the above technical problems, the purpose of the present invention is to provide a sodium ion battery layered oxide positive electrode material and a preparation method and application thereof. The prepared fluoride ion and rare earth metal ion co-doped P2 phase sodium ion battery layered oxide positive electrode material has high specific capacity, good cycle stability, is more stable when exposed to air, and has a simple preparation process, low cost, and is environmentally friendly, and is suitable for large-scale production.

[0006] The above object of the present invention is achieved through the following technical solutions: The first aspect of the present invention provides a sodium ion battery layered oxide positive electrode material, wherein the sodium ion battery layered oxide positive electrode material is Na 0.67 Mn a Fe b Ni c M x O 2-y F 2y , wherein M is a rare earth metal element, 0.55≤a≤0.65, 0.1≤b≤0.2, 0.05≤c≤0.15, 0<x≤0.1, 0<y≤0.1.

[0007] The sodium ion battery layered oxide positive electrode material provided by the present invention is a fluorine ion and rare earth metal ion co-doped P2 phase sodium ion battery layered oxide positive electrode material, wherein part of the fluorine ions occupy the oxygen site to replace the oxygen ions, and part of the rare earth metal ions occupy the transition metal site to replace the transition metal ions, and the transition metal ions and / or rare earth metal ions at the transition metal site form an octahedral structure with the six adjacent oxygen ions and / or fluorine ions, and are connected with the sodium ion layers coordinated by triangular prisms in a co-edge or co-plane manner and arranged alternately, forming a P2 type layered oxide material with a space group of P63-mmc.

[0008] Na 0.67 Mn a Fe b Ni c M x O 2-y F 2y In the formula, Mn, Fe, and Ni are transition metal elements, F is a fluorine element that is doped to replace the oxygen site, and M is a rare earth metal element that is doped to replace the transition metal site. The values ​​of a, b, c, x, and y satisfy the charge balance of the chemical formula.

[0009] Preferably, 0.01<x≤0.05.

[0010] Preferably, 0.005<y≤0.05.

[0011] Furthermore, the molar ratio of the rare earth metal element to the fluorine element is (0.1-10):1, preferably (0.5-5):1, and more preferably 1:1.

[0012] Furthermore, the rare earth metal element is selected from one or more of cerium (Ce), lanthanum (La), yttrium (Y), scandium (Sc), praseodymium (Pr), neodymium (Nd), promethium (Pm), samarium (Sm), ytterbium (Yb), europium (Eu) and lutetium (Lu).

[0013] Furthermore, the rare earth metal ion is selected from Ce 4+ ,La 3+ , Pr 4+ , Y 3+ Sc 3+ 、Nd 3+ 、Pm 3+ 、Sm 3+ 、Eu 3+ , Yb 3+ He Lu 3+ One or more of the .

[0014] The second aspect of the present invention provides a method for preparing the above-mentioned sodium ion battery layered oxide positive electrode material, which is a solid phase method and comprises the following steps: (1) dispersing a manganese source, an iron source, a nickel source, a rare earth metal source, a fluorine source and a sodium source in a solvent according to a preset molar ratio to obtain a solid-liquid mixture, subjecting the solid-liquid mixture to ball milling to obtain a precursor slurry, and removing the solvent from the precursor slurry to obtain a precursor powder; (2) The precursor powder is pre-sintered at 400-600°C, and then calcined at 800-1000°C to obtain the sodium ion battery layered oxide positive electrode material.

[0015] Furthermore, in step (1), the solvent is one or more of ethanol, isopropanol, acetone and ketone.

[0016] Furthermore, in step (1), the manganese source is selected from one or more of manganese dioxide, manganese acetate, manganese sulfate, manganese chloride and manganese nitrate.

[0017] Furthermore, in step (1), the iron source is selected from one or more of ferric oxide, ferrous oxide, ferrous acetate, ferric acetate, ferric sulfate, ferric chloride, ferric nitrate and ferric hydroxide.

[0018] Furthermore, in step (1), the nickel source is selected from one or more of nickel oxide, nickel acetate, nickel sulfate, nickel chloride and nickel nitrate.

[0019] Furthermore, in step (1), the rare earth metal source is selected from one or more of oxides, acetates, sulfates, chlorides and nitrates of cerium, lanthanum, yttrium, scandium, praseodymium, neodymium, promethium, samarium, ytterbium, europium and lutetium.

[0020] Furthermore, in step (1), the fluorine source is selected from sodium fluoride and / or ammonium fluoride.

[0021] Furthermore, in step (1), the sodium source is selected from one or more of sodium oxalate, sodium nitrate, sodium hydroxide, sodium peroxide, sodium carbonate, sodium chloride, sodium citrate, sodium fluoride and sodium acetate.

[0022] Furthermore, in step (1), the sodium source needs to be added in excess, with the addition range being 1-1.05 times the actual required amount.

[0023] Furthermore, in step (1), the total concentration of the manganese source, iron source, nickel source, rare earth metal source, fluorine source and sodium source in the solid-liquid mixture is 0.2-0.35 g / mL.

[0024] Furthermore, in step (1), the ball milling treatment is carried out at a rotation speed of 400-600 rpm and for a time of 10-24 h.

[0025] Furthermore, in step (1), the specific method for removing the solvent is: drying the precursor slurry at 80-100° C. for 6-12 h.

[0026] Furthermore, in step (2), the pre-sintering treatment is carried out by heating the temperature to 400-600°C at a heating rate of 3-5°C / min and keeping the temperature for 6-12 hours.

[0027] Furthermore, in step (2), the calcination treatment is carried out by heating the temperature to 800-1000°C at a heating rate of 3-5°C / min and keeping the temperature for 12-24 hours. The calcination temperature is preferably 850-950°C.

[0028] In a specific embodiment, the preparation method comprises the following steps: (1) According to the chemical formula of the sodium ion battery layered oxide positive electrode material, a manganese source, an iron source, a nickel source, a rare earth metal source, a fluorine source and a sodium source are weighed in a stoichiometric ratio, and the mixture is dispersed in a solvent to obtain a solid-liquid mixture; the solid-liquid mixture is placed in a ball milling jar, and ball milled using a planetary ball mill to obtain a precursor slurry; the precursor slurry is placed in an oven, and after removing the solvent, the precursor slurry is crushed, ground and sieved to obtain a precursor powder; (2) placing the precursor powder in a muffle furnace, and pre-calcining the powder at 400-600°C in an air atmosphere to obtain a pre-calcined product; then placing the pre-calcined product in a tube furnace, and calcining the powder at 800-1000°C in an air atmosphere, and naturally cooling the powder to room temperature, and then grinding and sieving the powder again to obtain the sodium ion battery layered oxide positive electrode material.

[0029] In a specific embodiment, in step (1), the volume of the solid-liquid mixture accounts for 1 / 2-2 / 3 of the volume of the ball mill.

[0030] The third aspect of the present invention provides the use of the sodium ion battery layered oxide positive electrode material described in the first aspect in assembling a sodium ion battery.

[0031] The fourth aspect of the present invention provides a sodium ion battery positive electrode plate, comprising the sodium ion battery layered oxide positive electrode material described in the first aspect.

[0032] A fifth aspect of the present invention provides a sodium ion battery, comprising the sodium ion battery layered oxide positive electrode material described in the first aspect.

[0033] Beneficial effects of the present invention: 1. The preparation method provided by the present invention adopts a simple high-temperature solid phase method, which is easy to operate, low in cost, environmentally friendly, and suitable for large-scale production.

[0034] 2. The present invention uses rare earth element doping to modify the surface of layered oxide positive electrode materials, effectively inhibiting the precipitation of lattice oxygen and reducing the occurrence of side reactions, thereby significantly improving the structural stability of nickel-iron-manganese-based sodium ion battery positive electrode materials; in addition, by doping fluorine ions with higher electronegativity than oxygen ions, the arrangement and distribution of transition metal elements nickel, iron, and manganese are disordered, which is beneficial to inhibiting the formation of Mn 3+ The structural distortion caused by the Jahn-Teller effect is further enhanced to further enhance the structural stability of the material. The present invention effectively inhibits the corrosion and damage of the electrolyte to the active material through the synergistic doping of rare earth metal ions and fluoride ions, improves the discharge specific capacity of the sodium ion battery, and significantly improves the cycle stability. This synergistic effect not only improves the electrochemical performance of the positive electrode material, but also prolongs the service life of the battery. BRIEF DESCRIPTION OF THE DRAWINGS

[0035] Figure 1 The XRD diagrams of the sodium ion battery layered oxide positive electrode materials prepared in Example 1 and Comparative Examples 1-2.

[0036] Figure 2 The SEM images of the sodium ion battery layered oxide positive electrode materials prepared in Example 1 and Comparative Example 1; wherein a) is the Na 0.67 Ni 0.15 Fe 0.2 Mn 0.65 O2, b) is Na in Example 1 0.67 Ni 0.15 Fe 0.2 Mn 0.61 Ce 0.04 O 1.9 6F0.04 .

[0037] Figure 3 Partial X-ray photoelectron spectroscopy (XPS) graphs of the sodium ion battery layered oxide positive electrode materials prepared in Example 1 and Comparative Examples 1-2; wherein (a) is the Mn element XPS graph of Comparative Example 1, (b) is the Mn element XPS graph of Comparative Example 2, (c) is the Mn element XPS graph of Example 1, (d) is the Ce element XPS graph of Comparative Example 2, and (e) is the Ce element XPS graph of Example 1.

[0038] Figure 4 This is a first cycle charge and discharge curve diagram of a sodium ion battery assembled with the sodium ion battery layered oxide positive electrode materials prepared in Example 1 and Comparative Example 1 at 0.05 C.

[0039] Figure 5 100 cycle images of a sodium ion battery assembled with the sodium ion battery layered oxide positive electrode materials prepared in Example 1 and Comparative Examples 1-3 after standing for 12 hours at a voltage window of 1.5-4.3 V and a current of 0.1 C.

[0040] Figure 6 The sodium ion battery assembled with the sodium ion battery layered oxide positive electrode materials prepared in Examples 1 and 9-12 was left to stand for 12 hours and had 100 cycle images at a voltage window of 1.5-4.3 V and a current of 0.1 C. DETAILED DESCRIPTION

[0041] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those commonly understood by those skilled in the art to which the present invention belongs. The terms used herein in the specification of the present invention are only for the purpose of describing specific embodiments and are not intended to limit the present invention. The term "and / or" used herein includes any and all combinations of one or more of the related listed items.

[0042] The present invention is further described below in conjunction with the accompanying drawings and specific embodiments so that those skilled in the art can better understand the present invention and implement it, but the embodiments are not intended to limit the present invention.

[0043] Unless otherwise specified, the experimental methods used in the following examples are all conventional methods, and the materials, reagents, etc. used are all available from commercial sources unless otherwise specified. Example 1

[0044] A layered oxide positive electrode material for sodium ion batteries 0.67 Ni 0.15 Fe 0.2 Mn 0.61 Ce0.04 O 1.96 F 0.04 The preparation method adopts a high temperature solid phase method to prepare a fluoride ion and cerium ion co-doped P2 phase sodium ion battery layered oxide positive electrode material, comprising the following steps: (1) Sodium carbonate (Na2CO3), nickel oxide (NiO), iron oxide (Fe2O3), manganese dioxide (MnO2), cerium dioxide (CeO2) and sodium fluoride (NaF) were weighed according to the molar ratio of Na:Ni:Fe:Mn:Ce:F=7.035:1.5:2:6.1:0.4:0.4, dispersed in 30 mL of anhydrous ethanol, placed in a 50 mL ball mill, and ball milled at 400 rpm for 12 h using a planetary ball mill to obtain a precursor slurry; the precursor slurry was placed in an oven and dried at 80 °C to remove ethanol, then fully crushed and ground in a mortar, and sieved with a 400-mesh grading sieve to obtain a precursor powder.

[0045] (2) placing the precursor powder in a muffle furnace, heating the temperature to 400°C at a heating rate of 5°C / min in an air atmosphere for pre-sintering, and keeping the temperature for 8 hours to obtain a pre-sintered product; then placing the pre-sintered product in a tube furnace, heating the temperature to 850°C at a heating rate of 5°C / min in an air atmosphere for calcining, keeping the temperature for 12 hours, cooling naturally to room temperature, and grinding and sieving again to obtain Na 0.67 Ni 0.15 Fe 0.2 Mn 0.61 Ce 0.04 O 1.96 F 0.04 . Example 2

[0046] A layered oxide positive electrode material for sodium ion batteries 0.67 Ni 0.15 Fe 0.2 Mn 0.6 La 0.05 O 1.95 F 0.05 The preparation method adopts a high temperature solid phase method to prepare a fluoride ion and lanthanum ion co-doped P2 phase sodium ion battery layered oxide positive electrode material, comprising the following steps: (1) Sodium acetate (CH3COONa), nickel oxide (NiO), iron oxide (Fe2O3), manganese dioxide (MnO2), lanthanum nitrate (La(NO3)3)3) and sodium fluoride (NaF) were weighed in a molar ratio of Na:Ni:Fe:Mn:La:F=7.035:1.5:2:6:0.5:0.5, dispersed in 30 mL of anhydrous ethanol, placed in a 50 mL ball mill, and ball milled at 500 rpm for 16 h using a planetary ball mill to obtain a precursor slurry; the precursor slurry was placed in an oven and dried at 85 °C to remove ethanol, then fully crushed and ground in a mortar, and sieved with a 400-mesh grading sieve to obtain a precursor powder.

[0047] (2) placing the precursor powder in a muffle furnace, heating the temperature to 500°C at a heating rate of 5°C / min in an air atmosphere for pre-sintering, and keeping the temperature for 6 hours to obtain a pre-sintered product; then placing the pre-sintered product in a tube furnace, heating the temperature to 900°C at a heating rate of 5°C / min in an air atmosphere for calcining, keeping the temperature for 16 hours, cooling naturally to room temperature, and grinding and sieving again to obtain Na 0.67 Ni 0.15 Fe 0.2 Mn 0.6 La 0.05 O 1.95 F 0.05 . Example 3

[0048] A layered oxide positive electrode material for sodium ion batteries 0.67 Ni 0.15 Fe 0.2 Mn 0.6 Nd 0.05 O 1.95 F 0.05 The preparation method adopts a high temperature solid phase method to prepare a fluoride ion and neodymium ion co-doped P2 phase sodium ion battery layered oxide positive electrode material, comprising the following steps: (1) Sodium acetate (CH3COONa), nickel oxide (NiO), iron oxide (Fe2O3), manganese dioxide (MnO2), neodymium oxide (Nd2O3) and sodium fluoride (NaF) were weighed in a molar ratio of Na:Ni:Fe:Mn:Nd:F=7.035:1.5:2:6:0.5:0.5, dispersed in 30 mL of anhydrous ethanol, placed in a 50 mL ball mill, and ball milled at 550 rpm for 14 h using a planetary ball mill to obtain a precursor slurry; the precursor slurry was placed in an oven and dried at 95 °C to remove ethanol, then fully crushed and ground in a mortar, and sieved with a 400-mesh grading sieve to obtain a precursor powder.

[0049] (2) placing the precursor powder in a muffle furnace, heating the temperature to 500°C at a heating rate of 5°C / min in an air atmosphere for pre-sintering, and keeping the temperature for 6 hours to obtain a pre-sintered product; then placing the pre-sintered product in a tube furnace, heating the temperature to 950°C at a heating rate of 5°C / min in an air atmosphere for calcining, keeping the temperature for 18 hours, cooling naturally to room temperature, and grinding and sieving again to obtain Na 0.67 Ni 0.15 Fe 0.2 Mn 0.6 Nd 0.05 O 1.95 F 0.05 . Example 4

[0050] A layered oxide positive electrode material for sodium ion batteries 0.67 Ni 0.15 Fe 0.2 Mn 0.6 Yb 0.05 O 1.95 F 0.05 The preparation method adopts a high temperature solid phase method to prepare a fluorine ion and ytterbium ion co-doped P2 phase sodium ion battery layered oxide positive electrode material, comprising the following steps: (1) Sodium acetate (CH3COONa), nickel oxide (NiO), iron oxide (Fe2O3), manganese dioxide (MnO2), ytterbium oxide (Yb2O3) and sodium fluoride (NaF) were weighed in a molar ratio of Na:Ni:Fe:Mn:Yb:F=7.035:1.5:2:6:0.5:0.5, dispersed in 30 mL of anhydrous ethanol, placed in a 50 mL ball mill, and ball milled at 600 rpm for 16 h using a planetary ball mill to obtain a precursor slurry; the precursor slurry was placed in an oven and dried at 90 °C to remove ethanol, then fully crushed and ground in a mortar, and sieved with a 400-mesh grading sieve to obtain a precursor powder.

[0051] (2) placing the precursor powder in a muffle furnace, heating the temperature to 600°C at a heating rate of 5°C / min in an air atmosphere for pre-sintering, and keeping the temperature for 6 hours to obtain a pre-sintered product; then placing the pre-sintered product in a tube furnace, heating the temperature to 900°C at a heating rate of 5°C / min in an air atmosphere for calcining, keeping the temperature for 18 hours, cooling naturally to room temperature, and grinding and sieving again to obtain Na 0.67 Ni 0.15 Fe 0.2 Mn 0.6 Yb 0.05 O1.95 F 0.05 . Example 5

[0052] A layered oxide positive electrode material for sodium ion batteries 0.67 Ni 0.15 Fe 0.2 Mn 0.6 Y 0.05 O 1.95 F 0.05 The preparation method adopts a high temperature solid phase method to prepare a fluoride ion and yttrium ion co-doped P2 phase sodium ion battery layered oxide positive electrode material, comprising the following steps: (1) Sodium acetate (CH3COONa), nickel oxide (NiO), iron oxide (Fe2O3), manganese dioxide (MnO2), yttrium oxide (Y2O3) and sodium fluoride (NaF) were weighed in a molar ratio of Na:Ni:Fe:Mn:Y:F=7.035:1.5:2:6:0.5:0.5, dispersed in 30 mL of anhydrous ethanol, placed in a 50 mL ball mill, and ball milled at 560 rpm for 12 h using a planetary ball mill to obtain a precursor slurry; the precursor slurry was placed in an oven and dried at 85 °C to remove ethanol, then fully crushed and ground in a mortar, and sieved with a 400-mesh grading sieve to obtain a precursor powder.

[0053] (2) placing the precursor powder in a muffle furnace, heating the temperature to 550°C at a heating rate of 5°C / min in an air atmosphere for pre-sintering, and keeping the temperature for 6 hours to obtain a pre-sintered product; then placing the pre-sintered product in a tube furnace, heating the temperature to 950°C at a heating rate of 5°C / min in an air atmosphere for calcining, keeping the temperature for 18 hours, cooling naturally to room temperature, and grinding and sieving again to obtain Na 0.67 Ni 0.15 Fe 0.2 Mn 0.6 Y 0.05 O 1.95 F 0.05 . Example 6

[0054] A layered oxide positive electrode material for sodium ion batteries 0.67 Ni 0.15 Fe 0.2 Mn 0.6 Ce 0.02 Y 0.03 O 1.95 F 0.05 The preparation method adopts a high temperature solid phase method to prepare a P2 phase sodium ion battery layered oxide positive electrode material co-doped with fluoride ions, cerium ions and yttrium ions, comprising the following steps: (1) Sodium acetate (CH3COONa), nickel oxide (NiO), iron oxide (Fe2O3), manganese dioxide (MnO2), cerium dioxide (CeO2), yttrium oxide (Y2O3) and sodium fluoride (NaF) were weighed according to the molar ratio of Na:Ni:Fe:Mn:Ce:Y:F=7.035:1.5:2:6:0.2:0.3:0.5, dispersed in 30 mL of anhydrous ethanol, placed in a 50 mL ball mill, and ball milled at 560 rpm for 12 h using a planetary ball mill to obtain a precursor slurry; the precursor slurry was placed in an oven and dried at 85 °C to remove ethanol, then fully crushed and ground in a mortar, and sieved with a 400-mesh grading sieve to obtain a precursor powder.

[0055] (2) placing the precursor powder in a muffle furnace, heating the temperature to 550°C at a heating rate of 5°C / min in an air atmosphere for pre-sintering, and keeping the temperature for 6 hours to obtain a pre-sintered product; then placing the pre-sintered product in a tube furnace, heating the temperature to 850°C at a heating rate of 5°C / min in an air atmosphere for calcining, keeping the temperature for 18 hours, cooling naturally to room temperature, and grinding and sieving again to obtain Na 0.67 Ni 0.15 Fe 0.2 Mn 0.6 Ce 0.02 Y 0.03 O 1.95 F 0.05 . Example 7

[0056] A layered oxide positive electrode material for sodium ion batteries 0.67 Ni 0.15 Fe 0.2 Mn 0.6 Ce 0.03 La 0.02 O 1.95 F 0.05 The preparation method adopts a high temperature solid phase method to prepare a P2 phase sodium ion battery layered oxide positive electrode material co-doped with fluorine ions, cerium ions and lanthanum ions, comprising the following steps: (1) Sodium acetate (CH3COONa), nickel oxide (NiO), iron oxide (Fe2O3), manganese dioxide (MnO2), cerium dioxide (CeO2), lanthanum nitrate (La(NO3)3)3) and sodium fluoride (NaF) were weighed in a molar ratio of Na:Ni:Fe:Mn:Ce:La:F=7.035:1.5:2:6:0.3:0.2:0.5, dispersed in 30 mL of anhydrous ethanol, placed in a 50 mL ball mill, and ball milled at 560 rpm for 12 h using a planetary ball mill to obtain a precursor slurry; the precursor slurry was placed in an oven and dried at 85 °C to remove ethanol, then fully crushed and ground in a mortar, and sieved with a 400-mesh grading sieve to obtain a precursor powder.

[0057] (2) placing the precursor powder in a muffle furnace, heating the temperature to 550°C at a heating rate of 5°C / min in an air atmosphere for pre-sintering, and keeping the temperature for 6 hours to obtain a pre-sintered product; then placing the pre-sintered product in a tube furnace, heating the temperature to 900°C at a heating rate of 5°C / min in an air atmosphere for calcining, keeping the temperature for 15 hours, cooling naturally to room temperature, and grinding and sieving again to obtain Na 0.67 Ni 0.15 Fe 0.2 Mn 0.6 Ce 0.03 La 0.02 O 1.95 F 0.05 . Example 8

[0058] A layered oxide positive electrode material for sodium ion batteries 0.67 Ni 0.15 Fe 0.2 Mn 0.6 Ce 0.02 La 0.02 Y 0.01 O 1.9 5F 0.05 The preparation method adopts a high temperature solid phase method to prepare a P2 phase sodium ion battery layered oxide positive electrode material co-doped with fluoride ions, cerium ions, lanthanum ions, and yttrium ions, comprising the following steps: (1) Sodium acetate (CH3COONa), nickel oxide (NiO), iron oxide (Fe2O3), manganese dioxide (MnO2), cerium dioxide (CeO2), lanthanum nitrate (La(NO3)3), yttrium oxide (Y2O3) and sodium fluoride (NaF) were weighed in a molar ratio of Na:Ni:Fe:Mn:Ce:La:Y:F=7.035:1.5:2:6:0.2:0.2:0.1:0.5, dispersed in 30 mL of anhydrous ethanol, placed in a 50 mL ball mill, and ball milled at 560 rpm for 15 h using a planetary ball mill to obtain a precursor slurry; the precursor slurry was placed in an oven and dried at 85 °C to remove ethanol, then fully crushed and ground in a mortar, and sieved with a 400-mesh grading sieve to obtain a precursor powder.

[0059] (2) placing the precursor powder in a muffle furnace, heating the temperature to 550°C at a heating rate of 5°C / min in an air atmosphere for pre-sintering, and keeping the temperature for 6 hours to obtain a pre-sintered product; then placing the pre-sintered product in a tube furnace, heating the temperature to 800°C at a heating rate of 5°C / min in an air atmosphere for calcining, keeping the temperature for 20 hours, cooling naturally to room temperature, and grinding and sieving again to obtain Na 0.67 Ni 0.15 Fe 0.2 Mn 0.6 Ce 0.02 La 0.02 Y 0.01 O 1.95 F 0.05 . Example 9

[0060] A layered oxide positive electrode material for sodium ion batteries 0.67 Ni 0.15 Fe 0.2 Mn 0.64 Ce 0.01 O 1.99 F 0.01 The preparation method adopts a high temperature solid phase method to prepare a fluoride ion and cerium ion doped P2 phase sodium ion battery layered oxide positive electrode material, comprising the following steps: (1) Sodium carbonate (Na2CO3), nickel oxide (NiO), iron oxide (Fe2O3), manganese dioxide (MnO2), cerium dioxide (CeO2) and sodium fluoride (NaF) were weighed according to the molar ratio of Na:Ni:Fe:Mn:Ce:F=7.035:1.5:2:6.4:0.1:0.1, dispersed in 30 mL of anhydrous ethanol, placed in a 50 mL ball mill, and ball milled at 400 rpm for 12 h using a planetary ball mill to obtain a precursor slurry; the precursor slurry was placed in an oven and dried at 80 °C to remove ethanol, then fully crushed and ground in a mortar, and sieved with a 400-mesh grading sieve to obtain a precursor powder.

[0061] (2) placing the precursor powder in a muffle furnace, heating the temperature to 400°C at a heating rate of 5°C / min in an air atmosphere for pre-sintering, and keeping the temperature for 8 hours to obtain a pre-sintered product; then placing the pre-sintered product in a tube furnace, heating the temperature to 850°C at a heating rate of 5°C / min in an air atmosphere for calcining, keeping the temperature for 12 hours, cooling naturally to room temperature, and grinding and sieving again to obtain Na 0.67 Ni 0.15 Fe 0.2 Mn 0.64 Ce 0.01 O 1.99 F 0.01 . Example 10

[0062] A layered oxide positive electrode material for sodium ion batteries 0.67 Ni 0.15 Fe 0.2 Mn 0.63 Ce 0.02 O 1.98 F 0.02 The preparation method adopts a high temperature solid phase method to prepare a fluoride ion and cerium ion doped P2 phase sodium ion battery layered oxide positive electrode material, comprising the following steps: (1) Sodium carbonate (Na2CO3), nickel oxide (NiO), iron oxide (Fe2O3), manganese dioxide (MnO2), cerium dioxide (CeO2) and sodium fluoride (NaF) were weighed according to the molar ratio of Na:Ni:Fe:Mn:Ce:F=7.035:1.5:2:6.3:0.2:0.2, dispersed in 30 mL of anhydrous ethanol, placed in a 50 mL ball mill, and ball milled at 400 rpm for 12 h using a planetary ball mill to obtain a precursor slurry; the precursor slurry was placed in an oven and dried at 80 °C to remove ethanol, then fully crushed and ground in a mortar, and sieved with a 400-mesh grading sieve to obtain a precursor powder.

[0063] (2) placing the precursor powder in a muffle furnace, heating the temperature to 400°C at a heating rate of 5°C / min in an air atmosphere for pre-sintering, and keeping the temperature for 8 hours to obtain a pre-sintered product; then placing the pre-sintered product in a tube furnace, heating the temperature to 850°C at a heating rate of 5°C / min in an air atmosphere for calcining, keeping the temperature for 12 hours, cooling naturally to room temperature, and grinding and sieving again to obtain Na 0.67 Ni 0.15 Fe 0.2 Mn 0.63 Ce 0.02 O 1.98 F 0.02 . Embodiment 11

[0064] A layered oxide positive electrode material for sodium ion batteries 0.67 Ni 0.15 Fe 0.2 Mn 0.62 Ce 0.03 O 1.97 F 0.03 The preparation method adopts a high temperature solid phase method to prepare a fluoride ion and cerium ion doped P2 phase sodium ion battery layered oxide positive electrode material, comprising the following steps: (1) Sodium carbonate (Na2CO3), nickel oxide (NiO), iron oxide (Fe2O3), manganese dioxide (MnO2), cerium dioxide (CeO2) and sodium fluoride (NaF) were weighed according to the molar ratio of Na:Ni:Fe:Mn:Ce:F=7.035:1.5:2:6.2:0.3:0.3, dispersed in 30 mL of anhydrous ethanol, placed in a 50 mL ball mill, and ball milled at 400 rpm for 12 h using a planetary ball mill to obtain a precursor slurry; the precursor slurry was placed in an oven and dried at 80 °C to remove ethanol, then fully crushed and ground in a mortar, and sieved with a 400-mesh grading sieve to obtain a precursor powder.

[0065] (2) placing the precursor powder in a muffle furnace, heating the temperature to 400°C at a heating rate of 5°C / min in an air atmosphere for pre-sintering, and keeping the temperature for 8 hours to obtain a pre-sintered product; then placing the pre-sintered product in a tube furnace, heating the temperature to 850°C at a heating rate of 5°C / min in an air atmosphere for calcining, keeping the temperature for 12 hours, cooling naturally to room temperature, and grinding and sieving again to obtain Na 0.67 Ni 0.15 Fe 0.2 Mn 0.62 Ce 0.03 O1.97 F 0.03 . Example 12

[0066] A layered oxide positive electrode material for sodium ion batteries 0.67 Ni 0.15 Fe 0.2 Mn 0.6 Ce 0.05 O 1.95 F 0.05 The preparation method adopts a high temperature solid phase method to prepare a fluoride ion and cerium ion doped P2 phase sodium ion battery layered oxide positive electrode material, comprising the following steps: (1) Sodium carbonate (Na2CO3), nickel oxide (NiO), iron oxide (Fe2O3), manganese dioxide (MnO2), cerium dioxide (CeO2) and sodium fluoride (NaF) were weighed according to the molar ratio of Na:Ni:Fe:Mn:Ce:F=7.035:1.5:2:6:0.5:0.5, dispersed in 30 mL of anhydrous ethanol, placed in a 50 mL ball mill, and ball milled at 400 rpm for 12 h using a planetary ball mill to obtain a precursor slurry; the precursor slurry was placed in an oven and dried at 80 °C to remove ethanol, then fully crushed and ground in a mortar, and sieved with a 400-mesh grading sieve to obtain a precursor powder.

[0067] (2) placing the precursor powder in a muffle furnace, heating the temperature to 400°C at a heating rate of 5°C / min in an air atmosphere for pre-sintering, and keeping the temperature for 8 hours to obtain a pre-sintered product; then placing the pre-sintered product in a tube furnace, heating the temperature to 850°C at a heating rate of 5°C / min in an air atmosphere for calcining, keeping the temperature for 12 hours, cooling naturally to room temperature, and grinding and sieving again to obtain Na 0.67 Ni 0.15 Fe 0.2 Mn 0.6 Ce 0.05 O 1.95 F 0.05 . Example 13

[0068] A layered oxide positive electrode material for sodium ion batteries 0.67 Ni 0.15 Fe 0.2 Mn 0.6 Ce 0.05 O 1.99 F 0.01 The preparation method adopts a high temperature solid phase method to prepare a fluoride ion and cerium ion doped P2 phase sodium ion battery layered oxide positive electrode material, comprising the following steps: (1) Sodium carbonate (Na2CO3), nickel oxide (NiO), iron oxide (Fe2O3), manganese dioxide (MnO2), cerium dioxide (CeO2) and sodium fluoride (NaF) were weighed according to the molar ratio of Na:Ni:Fe:Mn:Ce:F=7.035:1.5:2:6:0.5:0.1, dispersed in 30 mL of anhydrous ethanol, placed in a 50 mL ball mill, and ball milled at 400 rpm for 12 h using a planetary ball mill to obtain a precursor slurry; the precursor slurry was placed in an oven and dried at 80 °C to remove ethanol, then fully crushed and ground in a mortar, and sieved with a 400-mesh grading sieve to obtain a precursor powder.

[0069] (2) placing the precursor powder in a muffle furnace, heating the temperature to 400°C at a heating rate of 5°C / min in an air atmosphere for pre-sintering, and keeping the temperature for 8 hours to obtain a pre-sintered product; then placing the pre-sintered product in a tube furnace, heating the temperature to 850°C at a heating rate of 5°C / min in an air atmosphere for calcining, keeping the temperature for 12 hours, cooling naturally to room temperature, and grinding and sieving again to obtain Na 0.67 Ni 0.15 Fe 0.2 Mn 0.6 Ce 0.05 O 1.99 F 0.01 . Embodiment 14

[0070] A layered oxide positive electrode material for sodium ion batteries 0.67 Ni 0.15 Fe 0.2 Mn 0.6 Ce 0.05 O 1.9 F 0.1 The preparation method adopts a high temperature solid phase method to prepare a fluoride ion and cerium ion doped P2 phase sodium ion battery layered oxide positive electrode material, comprising the following steps: (1) Sodium carbonate (Na2CO3), nickel oxide (NiO), iron oxide (Fe2O3), manganese dioxide (MnO2), cerium dioxide (CeO2) and sodium fluoride (NaF) were weighed according to the molar ratio of Na:Ni:Fe:Mn:Ce:F=7.035:1.5:2:6:0.5:1, dispersed in 30 mL of anhydrous ethanol, placed in a 50 mL ball mill, and ball milled at 400 rpm for 12 h using a planetary ball mill to obtain a precursor slurry; the precursor slurry was placed in an oven and dried at 80 °C to remove ethanol, then fully crushed and ground in a mortar, and sieved with a 400-mesh grading sieve to obtain a precursor powder.

[0071] (2) placing the precursor powder in a muffle furnace, heating the temperature to 400°C at a heating rate of 5°C / min in an air atmosphere for pre-sintering, and keeping the temperature for 8 hours to obtain a pre-sintered product; then placing the pre-sintered product in a tube furnace, heating the temperature to 850°C at a heating rate of 5°C / min in an air atmosphere for calcining, keeping the temperature for 12 hours, cooling naturally to room temperature, and grinding and sieving again to obtain Na 0.67 Ni 0.15 Fe 0.2 Mn 0.6 Ce 0.05 O 1.9 F 0.1 . Embodiment 15

[0072] A layered oxide positive electrode material for sodium ion batteries 0.67 Ni 0.15 Fe 0.2 Mn 0.55 Ce 0.1 O 1.8 F 0.2 The preparation method adopts a high temperature solid phase method to prepare a fluoride ion and cerium ion doped P2 phase sodium ion battery layered oxide positive electrode material, comprising the following steps: (1) Sodium carbonate (Na2CO3), nickel oxide (NiO), iron oxide (Fe2O3), manganese dioxide (MnO2), cerium dioxide (CeO2) and sodium fluoride (NaF) were weighed according to the molar ratio of Na:Ni:Fe:Mn:Ce:F=7.035:1.5:2:5.5:1:2, dispersed in 30 mL of anhydrous ethanol, placed in a 50 mL ball mill, and ball milled at 400 rpm for 12 h using a planetary ball mill to obtain a precursor slurry; the precursor slurry was placed in an oven and dried at 80 °C to remove ethanol, then fully crushed and ground in a mortar, and sieved with a 400-mesh sieve to obtain a precursor powder.

[0073] (2) placing the precursor powder in a muffle furnace, heating the temperature to 400°C at a heating rate of 5°C / min in an air atmosphere for pre-sintering, and keeping the temperature for 8 hours to obtain a pre-sintered product; then placing the pre-sintered product in a tube furnace, heating the temperature to 850°C at a heating rate of 5°C / min in an air atmosphere for calcining, keeping the temperature for 12 hours, cooling naturally to room temperature, and grinding and sieving again to obtain Na 0.67 Ni 0.15 Fe 0.2 Mn 0.55 Ce 0.1 O 1.8 F0.2 . Comparative Example 1

[0074] A layered oxide positive electrode material for sodium ion batteries 0.67 Ni 0.15 Fe 0.2 Mn 0.65 The preparation method of O2 adopts a high temperature solid phase method to prepare an undoped P2 phase sodium ion battery layered oxide positive electrode material, comprising the following steps: (1) Sodium carbonate (Na2CO3), nickel oxide (NiO), iron oxide (Fe2O3) and manganese dioxide (MnO2) were weighed according to the molar ratio of Na:Ni:Fe:Mn =7.035:1.5:2:6.5, dispersed in 30 mL of anhydrous ethanol, placed in a 50 mL ball mill, and ball milled at 400 rpm for 12 h using a planetary ball mill to obtain a precursor slurry; the precursor slurry was placed in an oven and dried at 80 °C to remove ethanol, then fully crushed and ground in a mortar, and sieved with a 400-mesh sieve to obtain a precursor powder.

[0075] (2) placing the precursor powder in a muffle furnace, heating the temperature to 400°C at a heating rate of 5°C / min in an air atmosphere for pre-sintering, and keeping the temperature for 8 hours to obtain a pre-sintered product; then placing the pre-sintered product in a tube furnace, heating the temperature to 850°C at a heating rate of 5°C / min in an air atmosphere for calcining, keeping the temperature for 12 hours, cooling naturally to room temperature, and grinding and sieving again to obtain Na 0.67 Ni 0.15 Fe 0.2 Mn 0.65 O2. Comparative Example 2

[0076] A layered oxide positive electrode material for sodium ion batteries 0.67 Ni 0.15 Fe 0.2 Mn 0.61 Ce 0.04 The preparation method of O2 adopts a high temperature solid phase method to prepare a cerium-doped P2 phase sodium ion battery layered oxide positive electrode material, comprising the following steps: (1) Sodium carbonate (Na2CO3), nickel oxide (NiO), iron oxide (Fe2O3), manganese dioxide (MnO2) and cerium nitrate (Ce(NO3)3) were weighed according to the molar ratio of Na:Ni:Fe:Mn:Ce=7.035:1.5:2:6.1:0.4, dispersed in 30 mL of anhydrous ethanol, placed in a 50 mL ball mill, and ball milled at 400 rpm for 12 h using a planetary ball mill to obtain a precursor slurry; the precursor slurry was placed in an oven and dried at 80 °C to remove ethanol, then fully crushed and ground in a mortar, and sieved with a 400-mesh sieve to obtain a precursor powder.

[0077] (2) placing the precursor powder in a muffle furnace, heating the temperature to 400°C at a heating rate of 5°C / min in an air atmosphere for pre-sintering, and keeping the temperature for 8 hours to obtain a pre-sintered product; then placing the pre-sintered product in a tube furnace, heating the temperature to 850°C at a heating rate of 5°C / min in an air atmosphere for calcining, keeping the temperature for 12 hours, cooling naturally to room temperature, and grinding and sieving again to obtain Na 0.67 Ni 0.15 Fe 0.2 Mn 0.61 Ce 0.04 O2. Comparative Example 3

[0078] A layered oxide positive electrode material for sodium ion batteries 0.67 Ni 0.15 Fe 0.2 Mn 0.65 O 1.97 F 0.03 The preparation method adopts a high temperature solid phase method to prepare a fluorine-doped P2 phase sodium ion battery layered oxide positive electrode material, comprising the following steps: (1) Sodium oxalate (Na2C2O4), nickel oxide (NiO), iron oxide (Fe2O3), manganese dioxide (MnO2) and sodium fluoride (NaF) were weighed according to the molar ratio of Na:Ni:Fe:Mn:F=7.035:1.5:2:6.5:0.3, dispersed in 30 mL of anhydrous ethanol, placed in a 50 mL ball mill, and ball milled at 400 rpm for 12 h using a planetary ball mill to obtain a precursor slurry; the precursor slurry was placed in an oven and dried at 80 °C to remove ethanol, then fully crushed and ground in a mortar, and sieved with a 400-mesh grading sieve to obtain a precursor powder.

[0079] (2) placing the precursor powder in a muffle furnace, heating the temperature to 400°C at a heating rate of 5°C / min in an air atmosphere for pre-sintering, and keeping the temperature for 8 hours to obtain a pre-sintered product; then placing the pre-sintered product in a tube furnace, heating the temperature to 850°C at a heating rate of 5°C / min in an air atmosphere for calcining, keeping the temperature for 12 hours, cooling naturally to room temperature, and grinding and sieving again to obtain Na 0.67 Ni 0.15 Fe 0.2 Mn 0.65 O 1.97 F 0.03 . Comparative Example 4

[0080] A layered oxide positive electrode material for sodium ion batteries 0.67 Ni 0.15 Fe 0.2 Mn 0.45 Ce 0.2 O 1.8 F 0.2 The preparation method adopts a high temperature solid phase method to prepare a fluoride ion and cerium ion co-doped P2 phase sodium ion battery layered oxide positive electrode material, comprising the following steps: (1) Sodium carbonate (Na2CO3), nickel oxide (NiO), iron oxide (Fe2O3), manganese dioxide (MnO2), cerium dioxide (CeO2) and sodium fluoride (NaF) were weighed according to the molar ratio of Na:Ni:Fe:Mn:Ce:F=7.035:1.5:2:4.5:2:2, dispersed in 30 mL of anhydrous ethanol, placed in a 50 mL ball mill, and ball milled at 400 rpm for 12 h using a planetary ball mill to obtain a precursor slurry; the precursor slurry was placed in an oven and dried at 80 °C to remove ethanol, then fully crushed and ground in a mortar, and sieved with a 400-mesh grading sieve to obtain a precursor powder.

[0081] (2) placing the precursor powder in a muffle furnace, heating the temperature to 400°C at a heating rate of 5°C / min in an air atmosphere for pre-sintering, and keeping the temperature for 8 hours to obtain a pre-sintered product; then placing the pre-sintered product in a tube furnace, heating the temperature to 850°C at a heating rate of 5°C / min in an air atmosphere for calcining, keeping the temperature for 12 hours, cooling naturally to room temperature, and grinding and sieving again to obtain Na 0.67 Ni 0.15 Fe 0.2 Mn 0.45 Ce 0.2 O 1.8 F 0.2 . Comparative Example 5

[0082] A layered oxide positive electrode material for sodium ion batteries 0.67 Ni 0.15 Fe 0.2 Mn 0.55 Ce 0.1 O 1.7 F 0.3 The preparation method adopts a high temperature solid phase method to prepare a fluoride ion and cerium ion co-doped P2 phase sodium ion battery layered oxide positive electrode material, comprising the following steps: (1) Sodium carbonate (Na2CO3), nickel oxide (NiO), iron oxide (Fe2O3), manganese dioxide (MnO2), cerium dioxide (CeO2) and sodium fluoride (NaF) were weighed according to the molar ratio of Na:Ni:Fe:Mn:Ce:F=7.035:1.5:2:5.5:1:3, dispersed in 30 mL of anhydrous ethanol, placed in a 50 mL ball mill, and ball milled at 400 rpm for 12 h using a planetary ball mill to obtain a precursor slurry; the precursor slurry was placed in an oven and dried at 80 °C to remove ethanol, then fully crushed and ground in a mortar, and sieved with a 400-mesh grading sieve to obtain a precursor powder.

[0083] (2) placing the precursor powder in a muffle furnace, heating the temperature to 400°C at a heating rate of 5°C / min in an air atmosphere for pre-sintering, and keeping the temperature for 8 hours to obtain a pre-sintered product; then placing the pre-sintered product in a tube furnace, heating the temperature to 850°C at a heating rate of 5°C / min in an air atmosphere for calcining, keeping the temperature for 12 hours, cooling naturally to room temperature, and grinding and sieving again to obtain Na 0.67 Ni 0.15 Fe 0.2 Mn 0.55 Ce 0.1 O 1.7 F 0.3 . Comparative Example 6

[0084] A layered oxide positive electrode material for sodium ion batteries 0.67 Ni 0.15 Fe 0.2 Mn 0.45 Ce 0.2 O 1.7 F 0.3 The preparation method adopts a high temperature solid phase method to prepare a fluoride ion and cerium ion co-doped P2 phase sodium ion battery layered oxide positive electrode material, comprising the following steps: (1) Sodium carbonate (Na2CO3), nickel oxide (NiO), iron oxide (Fe2O3), manganese dioxide (MnO2), cerium dioxide (CeO2) and sodium fluoride (NaF) were weighed according to the molar ratio of Na:Ni:Fe:Mn:Ce:F=7.035:1.5:2:5.5:1:3, dispersed in 30 mL of anhydrous ethanol, placed in a 50 mL ball mill, and ball milled at 400 rpm for 12 h using a planetary ball mill to obtain a precursor slurry; the precursor slurry was placed in an oven and dried at 80 °C to remove ethanol, then fully crushed and ground in a mortar, and sieved with a 400-mesh grading sieve to obtain a precursor powder.

[0085] (2) placing the precursor powder in a muffle furnace, heating the temperature to 400°C at a heating rate of 5°C / min in an air atmosphere for pre-sintering, and keeping the temperature for 8 hours to obtain a pre-sintered product; then placing the pre-sintered product in a tube furnace, heating the temperature to 850°C at a heating rate of 5°C / min in an air atmosphere for calcining, keeping the temperature for 12 hours, cooling naturally to room temperature, and grinding and sieving again to obtain Na 0.67 Ni 0.15 Fe 0.2 Mn 0.45 Ce 0.2 O 1.7 F 0.3 .

[0086] Figure 1 The X-ray diffraction (XRD) diagrams of the sodium ion battery layered oxide positive electrode materials prepared in Example 1 and Comparative Examples 1-2, wherein a is the pure phase P2 phase positive electrode material Na before modification in Comparative Example 1. 0.67 Ni 0.15 Fe 0.2 Mn 0.65 O2, b is the positive electrode material Na doped with rare earth metal element cerium ion in Comparative Example 2 0.67 Ni 0.15 Fe 0.2 Mn 0.61 Ce 0.04 O2, c is the positive electrode material Na2O2 co-doped with fluorine ions and cerium ions in Example 1 0.67 Ni 0.15 Fe 0.2 Mn 0.61 Ce 0.04 O 1.96 F 0.04The structures of the three positive electrode materials are basically the same, which conforms to the basic characteristics of the P2 phase layered oxide of the standard PDF card, indicating that the composite metal oxide coating layer does not cause the structure of the positive electrode material to change, and the cerium ion-doped positive electrode material generates characteristic peaks of CeO2 at 2θ=28.6°, 33.2°, 47.6°, and 56.5°.

[0087] Figure 2 The scanning electron microscope (SEM) images of the sodium ion battery layered oxide positive electrode materials prepared in Example 1 and Comparative Example 1; wherein a) is the Na 0.67 Ni 0.15 Fe 0.2 Mn 0.65 O2, b) is Na in Example 1 0.67 Ni 0.15 Fe 0.2 Mn 0.61 Ce 0.04 O 1.96 F 0.04 .from Figure 2 It can be seen that the morphology of the two cathode material particles is nanosheet structure, with smooth surface and dense structure; Figure 2 As can be seen in b), the primary particles become larger after co-doping with fluorine ions and cerium ions.

[0088] Figure 3 Partial X-ray photoelectron spectroscopy (XPS) graphs of the sodium ion battery layered oxide positive electrode materials prepared in Example 1 and Comparative Examples 1-2; wherein (a) is the Mn element XPS graph of Comparative Example 1, (b) is the Mn element XPS graph of Comparative Example 2, (c) is the Mn element XPS graph of Example 1, (d) is the Ce element XPS graph of Comparative Example 2, and (e) is the Ce element XPS graph of Example 1. Figure 3 It can be seen that in Comparative Example 1, Mn 3+ :Mn 4+ =3.8:6.2, Mn in Comparative Example 2 3+ :Mn 4+ =4.2:5.8, Mn in Comparative Example 3 3+ :Mn 4+ =3.5:6.5, indicating that the Mn content of the material after cerium ion doping and co-doping with fluorine ions and cerium ions 3+ The Mn 3+ Further reduction can effectively inhibit Mn 3+ The structural distortion caused by the Jahn-Teller effect of fluorine ions and cerium ions also shows that the fluorine ions and cerium ions produce a synergistic effect. 3+ :Ce4+ =9:16, after adding fluoride ions in Example 1, the ratio becomes Ce 3+ :Ce 4+ =5.1:4.9, indicating that part of the cerium ions were reduced from the original 4-valent to 3-valent, and more Ce 3+ Entering into the crystal lattice further expands the interplanar spacing, which is beneficial to the transmission of sodium ions, further illustrating that fluoride ions and cerium ions produce a good synergistic effect. Test Case

[0089] The sodium ion battery layered oxide positive electrode material prepared in Examples 1-15 and Comparative Examples 1-6 was used to assemble a sodium ion battery. The assembly method was as follows: the sodium ion battery layered oxide positive electrode material, the conductive agent Super P (SP) and the binder PVDF were ground uniformly at a mass ratio of 8:1:1, and then an appropriate amount of N-methylpyrrolidone (NMP) was added as a dispersant to prepare a slurry, which was evenly coated on an aluminum foil, dried at 80°C in a vacuum oven for 12 hours, and then cut into a circular positive electrode sheet with a diameter of 13 mm using a sheet cutter. Then, a metal sodium sheet with a diameter of 15.4 mm and a thickness of 0.45 mm was used as a negative electrode, a glass fiber with a diameter of 19 mm was used as a diaphragm, and a NaClO4 solution with a concentration of 1 M (wherein the solvent was a mixture of ethylene carbonate and dimethyl carbonate with a volume ratio of 1:1, plus 5% fluoroethylene carbonate) was used as an electrolyte, and a CR2032 button battery was assembled in a glove box filled with argon.

[0090] After the sodium ion batteries assembled with the sodium ion battery layered oxide positive electrode materials prepared in Examples 1-15 and Comparative Examples 1-6 were left to stand for 12 hours, their electrochemical properties were tested at a voltage window of 1.5-4.3 V and a current of 0.1 C. The test results are shown in Tables 1 and 2.

[0091] Table 1

[0092] Table 2

[0093] As can be seen from Table 1, rare earth metal ions enter the lattice after doping, which expands the interplanar spacing and is beneficial to the transmission of sodium ions. At the same time, the substitution of fluorine ions, which have higher electronegativity than oxygen ions, at the anion position is also beneficial to inhibit the Mn 3+Due to the structural distortion caused by the Jahn-Teller effect, Examples 1-8 all show excellent cycle stability. The extent to which the discharge specific capacity is increased after co-doping with different rare earth metal ions and fluoride ions is slightly different. At a suitable ratio, a good capacity improvement can be obtained compared to Comparative Example 1, and the first-cycle coulomb efficiency and 50-cycle capacity retention rate are also significantly increased. Among them, the positive electrode material of Example 1 has the highest first-cycle discharge specific capacity, which is 28.29% higher than that of Comparative Example 1, while Example 3 has the highest first-cycle coulomb efficiency and capacity retention rate after 50 cycles, indicating that different rare earth metal ions enter the lattice after doping, and the changes in the interplanar spacing and the transmission rate of sodium ions are different.

[0094] As can be seen from Table 2, after rare earth metal cerium ions and fluorine ions are co-doped, the effects of different doping ratios of fluorine ions and cerium ions on material properties are investigated, and the ratio of Example 1 is compared to be the best ratio. Comparing Example 1 with Examples 9-12, the cerium ions and fluorine ions are gradually increased from 0.01 to 0.05 in a ratio of 1:1, where the performance is best at a doping amount of 0.04, indicating that excessive doping of cerium ions and fluorine ions will affect the electrochemical properties of the positive electrode material. Comparing Example 1 with Examples 13-15, the doping ratio of cerium ions and fluorine ions is changed, but whether the cerium ions are increased or the fluorine ions are increased, the effect is not as good as the 1:1 ratio doping, and when the doping amount of cerium ions and fluorine ions reaches 0.1 or more, the performance of the positive electrode material has declined significantly. Comparing Example 1 with Comparative Examples 1-3, Example 1 co-doped with fluorine ions and cerium ions, taking into account the improvement of specific capacity and capacity retention rate on the basis of Comparative Examples 2 and Comparative Examples 3, and further improving the performance of the original positive electrode material of Comparative Example 1, which further illustrates that the doping of fluorine ions and cerium ions produces a good synergistic effect, which can significantly improve the performance of the positive electrode material. In Comparative Examples 4-6, the doping of fluorine ions and cerium ions is excessive, and the doping ratio of cerium ions to fluorine ions is too large, so that the performance of the positive electrode material is even lower than that of the undoped positive electrode material of the original Comparative Example 1. This is because the excessive doping of cerium ions and fluorine ions distorts the structure of the original positive electrode material, resulting in a serious decline in the performance of the positive electrode material.

[0095] Figure 4 The first cycle charge and discharge curve of the sodium ion battery assembled with the sodium ion battery layered oxide positive electrode material prepared in Example 1 and Comparative Example 1 at 0.05 C, wherein curve a is the first cycle charge and discharge curve of the sodium ion battery layered oxide positive electrode material prepared in Example 1 and Comparative Example 1 at 0.05 C. 0.67 Ni 0.15 Fe 0.2 Mn 0.65 O2, curve b is Na in Example 1 0.67 Ni 0.15 Fe 0.2 Mn 0.61 Ce0.04 O 1.96 F 0.04 .from Figure 4 It can be seen that the discharge capacity of the first cycle of Comparative Example 1 is 199.56 mAh / g, while the discharge capacity of the first cycle of Example 1 is increased to 218.35 mAh / g, indicating that co-doping of fluoride ions and cerium ions can significantly improve the performance of the positive electrode material.

[0096] Figure 5 The sodium ion battery assembled with the sodium ion battery layered oxide positive electrode material prepared in Example 1 and Comparative Examples 1-3 was left to stand for 12 hours and then cycled for 100 cycles at a voltage window of 1.5-4.3 V and a current of 0.1 C. Compared with Comparative Example 1, Comparative Example 2 shows that cerium ion doping can significantly improve the specific capacity and improve a certain capacity retention rate; Compared with Comparative Example 1 and Comparative Example 2, Comparative Example 3 shows that fluorine ion doping can effectively improve the capacity retention rate and also improve a certain specific capacity. Although the improved specific capacity is not as obvious as that of cerium ion doping, the capacity retention rate has been significantly improved; and Example 1, by co-doping fluorine ions with cerium ions, takes into account the improvement of specific capacity and capacity retention rate on the basis of Comparative Examples 2 and Comparative Examples 3, and further improves the performance of the original positive electrode material of Comparative Example 1. This further illustrates that fluorine ions and cerium ions produce a good synergistic effect, which can significantly improve the performance of positive electrode materials.

[0097] Figure 6 The sodium ion battery assembled with the sodium ion battery layered oxide positive electrode materials prepared in Examples 1 and 9-12 was left to stand for 12 hours, and 100 cycle images were taken at a voltage window of 1.5-4.3 V and a current of 0.1 C to investigate the effects of different doping ratios of fluoride ions and cerium ions on the material properties. By comparison, it was concluded that the ratio in Example 1 was the optimal ratio.

[0098] The fluorine ion and cerium ion co-doped positive electrode material prepared by the present invention can not only introduce cerium ions into the crystal lattice, increase the interplanar spacing, and promote the diffusion of sodium ions, but also grow some CeO2 on the surface of the sample, and at the same time produce a certain surface modification effect, which can inhibit the corrosion and damage of the electrolyte to the active material; doping with fluorine ions whose electronegativity is higher than that of oxygen ions makes the arrangement and distribution of transition metal elements nickel, iron, and manganese disordered, which is beneficial to inhibiting the Mn 3+ The structural distortion caused by the Jahn-Teller effect further enhances the structural stability of the material; through comparison of different comparative proportions, it can be seen that the synergistic effect of the two enhances the electrochemical properties and structural stability of the pure phase P2 phase positive electrode material before modification.

[0099] Obviously, the above embodiments of the present invention are only examples for clearly illustrating the present invention, and are not intended to limit the embodiments of the present invention. Those skilled in the art should understand that other different forms of changes or modifications can be made based on the above description. It is not necessary and impossible to list all the embodiments here. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present invention should be included in the protection scope of the claims of the present invention.

Claims

1. A sodium ion battery layered oxide positive electrode material, characterized in that: The sodium ion battery layered oxide positive electrode material is Na 0.67 Mn a Fe b Ni c M x O 2-y F 2y , wherein M is a rare earth metal element, 0.55≤a≤0.65, 0.1≤b≤0.2, 0.05≤c≤0.15, 0<x≤0.1, 0<y≤0.

1.

2. The sodium ion battery layered oxide positive electrode material according to claim 1, characterized in that: The rare earth metal element is selected from one or more of cerium, lanthanum, yttrium, scandium, praseodymium, neodymium, promethium, samarium, ytterbium, europium and lutetium.

3. The method for preparing the layered oxide positive electrode material for sodium ion batteries according to claim 1 or 2, characterized in that: The following steps are involved: (1) dispersing a manganese source, an iron source, a nickel source, a rare earth metal source, a fluorine source and a sodium source in a solvent according to a preset molar ratio to obtain a solid-liquid mixture, subjecting the solid-liquid mixture to ball milling to obtain a precursor slurry, and removing the solvent from the precursor slurry to obtain a precursor powder; (2) The precursor powder is pre-sintered at 400-600°C, and then calcined at 800-1000°C to obtain the sodium ion battery layered oxide positive electrode material.

4. The preparation method according to claim 3, characterized in that: In step (1), the manganese source is selected from one or more of manganese dioxide, manganese acetate, manganese sulfate, manganese chloride and manganese nitrate; The iron source is selected from one or more of ferric oxide, ferrous oxide, ferrous acetate, ferric acetate, ferric sulfate, ferric chloride, ferric nitrate and ferric hydroxide; The nickel source is selected from one or more of nickel oxide, nickel acetate, nickel sulfate, nickel chloride and nickel nitrate; The rare earth metal source is selected from one or more of oxides, acetates, sulfates, chlorides and nitrates of cerium, lanthanum, yttrium, scandium, praseodymium, neodymium, promethium, samarium, ytterbium, europium and lutetium; The fluorine source is selected from sodium fluoride and / or ammonium fluoride; The sodium source is selected from one or more of sodium oxalate, sodium nitrate, sodium hydroxide, sodium peroxide, sodium carbonate, sodium chloride, sodium citrate, sodium fluoride and sodium acetate.

5. The preparation method according to claim 3, characterized in that In step (1), the total concentration of the manganese source, iron source, nickel source, rare earth metal source, fluorine source and sodium source in the solid-liquid mixture is 0.2-0.35 g / mL.

6. The preparation method according to claim 3, characterized in that In step (1), the ball milling treatment is performed at a rotation speed of 400-600 rpm and for a time of 10-24 h.

7. The preparation method according to claim 3, characterized in that In step (2), the pre-sintering treatment is heated to 400-600°C at a heating rate of 3-5°C / min and kept at this temperature for 6-12 h; the calcining treatment is heated to 800-1000°C at a heating rate of 3-5°C / min and kept at this temperature for 12-24 h.

8. Use of the sodium ion battery layered oxide positive electrode material according to claim 1 or 2 in assembling a sodium ion battery.

9. A positive electrode sheet, characterized in that: The sodium ion battery layered oxide positive electrode material comprises the layered oxide positive electrode material according to claim 1 or 2.

10. A sodium ion battery, characterized in that: The invention comprises the sodium ion battery layered oxide positive electrode material according to claim 1 or 2.

Citation Information

Patent Citations

  • Manganese-based multi-element multi-site doped positive electrode material for sodium-ion battery and preparation method

    CN115180652A

  • Layered positive electrode material, preparation method thereof and application of layered positive electrode material in sodium-ion battery

    CN116534918A

  • Layered oxide positive electrode material of oxygen variable valence sodium ion battery and preparation method of layered oxide positive electrode material

    CN117199379A

Cited By

  • Layered transition metal oxide positive electrode material of sodium-ion battery as well as preparation method and application of layered transition metal oxide positive electrode material

    CN120646926A